How companies embed non-quantifiable product qualities through their product development process - Guldbrandsen, Marianne Norden (Cranfield University, 2006)
Many consumer products have reached a high level of technical product quality. Rapid adoption of new technologies and access to a global market means that markets are getting saturated. This means that technical differentiation is often not enough to sell a product and products compete more and more on intangible product qualities - these are meant to delight, bring pleasure, be easy to use and to create an experience. These qualities are often difficult to measure in the product using scientific descriptions and numerical measures. This research studies these Non-Quantifiable Product Qualities and the thesis presents research into how companies embed these Non-Quantifiable Product Qualities into their products in an attempt to satisfy their customers. The aim of this research was to gain insight into how large manufacturing companies embed product qualities that are difficult to quantify, by studying their product development process. This was done in two stages, firstly an exploratory study into five case organisations, secondly an in-depth study into three of the original five companies. Fifty interviews with designers, engineers and marketers formed the main source of data, supplemented with observations and document analysis. In the exploratory stage nine initial themes emerged out of data analysis, which then informed the data collection in the descriptive stage. The final output is seven confirmed themes, with 43 major findings and three conceptual models, that describe how companies embed Non-Quantifiable Product Qualities through their product development process. The research has found that the researched companies have some common strategies for embedding Non-Quantifiable Product Qualities. One example is that they will typically seek to translate an emotional response in the customer into measurable product qualities that will evoke such response. It is also common to seek out customer reaction to products during development to ensure successful embedding of Non-Quantifiable Product Qualities.